2010
DOI: 10.1186/1742-4682-7-17
|View full text |Cite
|
Sign up to set email alerts
|

A generalized physiologically-based toxicokinetic modeling system for chemical mixtures containing metals

Abstract: BackgroundHumans are routinely and concurrently exposed to multiple toxic chemicals, including various metals and organics, often at levels that can cause adverse and potentially synergistic effects. However, toxicokinetic modeling studies of exposures to these chemicals are typically performed on a single chemical basis. Furthermore, the attributes of available models for individual chemicals are commonly estimated specifically for the compound studied. As a result, the available models usually have parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…The current literature of metal induced neuronal damage is primarily confined to single metal exposure (Zhu et al, 2014) and no published literature was found on quaternary mixture of Pb, Cd, As and MeHg evoked toxicity. Metal mixture exposure and their mode of action relation evaluating either independent or addition and synergistic effects are not well developed (Rodríguez et al 1998;Sasso et al 2010). However, the evidence for these kind of interactions continue to grow (Stackelberg, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The current literature of metal induced neuronal damage is primarily confined to single metal exposure (Zhu et al, 2014) and no published literature was found on quaternary mixture of Pb, Cd, As and MeHg evoked toxicity. Metal mixture exposure and their mode of action relation evaluating either independent or addition and synergistic effects are not well developed (Rodríguez et al 1998;Sasso et al 2010). However, the evidence for these kind of interactions continue to grow (Stackelberg, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Further considerations include early life exposures such as in utero (Beaudouin et al 2010), through lactation (Verner et al 2008) and during infancy (Edginton and Ritter 2009). PBTK models are capable of capturing multiple chemical interactions at the level of metabolism; however, the lack of sufficient experimental data to describe the interaction terms has resulted in a limited number of applications so far, such as in the case of volatile organic compounds (VOCs) (Sarigiannis and Gotti 2008) and metals (Sasso et al 2010). PBTK models can also be used to reconstruct external exposure from HBM data.…”
Section: Toxicokinetic (Tk) and Physiology-based Toxicokinetic (Pbtk)mentioning
confidence: 99%
“…Figure 7 indicates that after 1-day exposure Cd was primarily accumulated in lungs (2.3 × 10 −4 µg) and in intestines (4.2 × 10 −5 µg) whereas after 35 days from initial intake accumulation was higher in other tissues (7.2 × 10 −5 µg), in kidney (5.3 × 10 −5 µg) and in liver (4.4 × 10 −5 µg). Several studies [98,109,110] found that Cd accumulates in kidney and liver. In addition, the WHO [110] suggests that the half-life of Cd in kidney is about 10-20 years with kidney damage being a primary health concern [109] because it is considered a critical target organ [32].…”
Section: Citymentioning
confidence: 99%